EVALUASI PELAKSANAAN EVENT SPORT TOURISM DALAM KEGIATAN TRIATHLON SUMATERA UTARA - Purba, Joen Parningotan; Siahaan, Jurdan Martin; br. payung, Milda Vinna (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
The implementation of tourism promotion activities on a national and international scale and combined with sports activities (sport tourism) is one of the events organized by the North Sumatra Provincial government. Analysis of the potential of tourism and sports objects in North Sumatra Province needs to be carried out a thorough study and identify the weaknesses and strengths of the location of these tourism and sports objects. Evaluation research is used to find out what activities have been carried out according to the expected goals. The subjects involved in this study amounted to 17 people consisting of the responsible person, the chief executive and 15 participants. The instruments used were questionnaires, interviews, observation and document analysis. Based on the sub context program evaluation which includes three things namely: 1) Legal Basis and Government Policy; 2) Purpose; 3) Targets can be categorized as Good. Evaluation of the sub Input program includes four things, namely: 1) Participants, 2) Implementation, 3) Funding, and 4) Committees can be categorized as Good. the evaluation of the sub Process program includes two things, namely: 1) competition regulations and, 2) implementation can be categorized as Good. Evaluation of the sub Process program includes two things, namely: 1) The level of participation and public interest, and 2) The role of the media in the publication and promotion of sports to the public can be categorized as Good. Based on the results of the study it can be concluded that the sport tourism Triathlon program can increase public interest in participation, the economy and the number of tourists who come because it is supported by government policies.